Missionaries, converts, and rabbis : the evangelical Alexander McCaul and Jewish-Christian debate in the nineteenth century - Ruderman, David B. (Jewish culture and contexts., 2020)
"This book is about the English missionary Alexander McCaul, who wrote many works aiming to convert Jews to Christianity. The book is about people who are caught between belief practices: philo-Semitisim, philo-Chrstianity, anti-Semitism, and anti-Christianity"--